Stakeholder Engagement in Sustainable Tourism Planning: Synthesising Freeman's Collaboration Theory and Bramwell's Tourism Governance Framework - Solahuddin Nasution; Safrizal Fazli Tarigan; Alifa Azzahra Nasution; Femmy I. Dalimunthe (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
Stakeholder engagement remains a key issue in sustainable tourism planning, especially in regional tourism contexts where meaningful participation is often limited by fragmented governance structures. This study synthesises Freeman’s stakeholder theory and Bramwell’s tourism governance framework to develop an integrated model of collaborative planning for heritage and coastal tourism destinations in North Sumatra Province. The study used a mixed-methods design involving structured surveys with 312 respondents, interviews with 28 key informants, and systematic field observations across six tourism destination clusters. The analysis mapped stakeholder influence-interest profiles, identified governance fragmentation, and examined the conditions that support collaborative planning in improving destination sustainability. The findings show that government-dominated governance, low power equality, and weak trust reciprocity tend to exclude local communities, traditional leaders, and civil society actors from strategic planning. This study develops a five-phase collaborative governance process model as an institutional design for sustainable tourism governance reform in North Sumatra. The model also offers relevance for other regional tourism systems in developing countries facing bureaucratic concentration and community marginalisation.